EXPLORING PRONUNCIATION CHALLENGES: INDONESIAN UNIVERSITY STUDENTS' PRODUCTION OF ENGLISH FRICATIVE SOUNDS - Luthfianda, Sahira; Irawan, Yusup; Rahayu, Ratih; Hidayat, Sarip (English Review: Journal of English Education, 2024)
Abstract: This study investigated the production of English alveolar and post-alveolar fricatives by 40 Indonesian university students who are not majoring in English study. The research instruments were a questionnaire, which was used to obtain information about the participants, and a word list, which was comprised of 16 English words with alveolar and post-alveolar fricatives and 9 tricky words. The results revealed two main findings. The first was that most Indonesian non-English major university students who participated in this research were not proficient in producing voiced post-alveolar fricative /ʒ/ which resulted in the substitution of the sound with /z/, /s/, and /ʃ/. The participants, however, were quite great at producing the voiceless post-alveolar fricative /ʃ/ and had no difficulty in producing alveolar fricatives /s/ and /z/. The second was that the results indicated that the participants’ problems in pronouncing English fricatives were mainly attributed to native language interference, the absence of the target sound in the sound system of their native language, and limited knowledge of English phonetics. This research recommends that EFL teachers give a special portion of time to train their students to pronounce fricative sounds in English that do not exist in the students' native language and provide them with English sound phonetic knowledge. Both of these things are strongly believed to improve the students’ proficiency in English pronunciation.